Is there heterogeneity in the response of consumption to income shocks? - Johannes Ludwig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
While recently more and more research has focused on the aggregate response of consumption to income shocks, little is known about how this response differs for households at different ends of the income distribution. This paper investigates how consumption reacts to transitory and permanent shocks to disposable income for households with an income above or below the median. Panel data on income and consumption from the PSID between 1998 and 2012 is used to estimate consumption insurance parameters. Although households below the median are found to be exposed to larger transitory and permanent income shocks, they can buffer permanent shocks to income significantly better compared to households above the median. The latter, though, are better insured against transitory income shocks. In general, the poorer households are, the more similarly they react to the two kinds of income shocks. – – Während sich viele Studien mit der durchschnittlichen Reaktion des Konsums auf Einkommensschocks befassen, ist wenig darüber bekannt, ob und wie sich diese Reaktion für Haushalte unterscheidet, die sich an unterschiedlichen Positionen in der Einkommensverteilung befinden. Diese Arbeit untersucht, wie Haushalte oberhalb und unterhalb des Medians ihren Konsum nach transitorischen und permanenten Schocks des verfügbaren Einkommens anpassen. Paneldaten des PSID zu Einkommen und Konsum für die Jahre von 1998 bis 2012 werden verwendet, um Konsumversicherungsparameter zu schätzen. Obwohl Haushalte unterhalb des Medians größeren transitorischen und permanenten Einkommensschocks ausgesetzt sind, gelingt es ihnen signifikant besser als Haushalten oberhalb des Medians, permanente Schocks abzufedern. Letztere sind aber besser in der Lage, transitorische Einkommensschocks zu bewältigen. Insgesamt zeigt sich, dass Haushalte umso ähnlicher auf beide Arten von Einkommensschocks reagieren, je ärmer sie sind.
Keywords: D12; D31; E21; 330; consumption response to income shocks; consumption insurance